Buyer’s willingness to pay for dwellings with different orientations - Song, Han-Suck; Wilhelmsson, Mats; Zheng, Mo (International Journal of Strategic Property Management, 2019)
This paper applies spatial hedonic econometric models to estimate the willingness of buyers to pay for dwellings with different orientations based on a data set comprising 63 306 transactions of secondhand apartment sales in 10 districts in Beijing from October 2011 to September 2014. Our results indicate that apartments with South orientation are sold at a 7.8% premium compared with those with West orientation, and that apartments in ancient city areas are more sensitive to orientation. The obtained results can help architects and developers to maximize the value of development projects by optimizing the layout of apartment units on each floor.